Sistem Monitoring Manajemen Baterai Perahu Listrik di Sayung Menggunakan Metode What If - Arif Fajar Nugroho; Supari; Pinandita, Satria (Elposys: Jurnal Sistem Kelistrikan, 2025)
The price of fuel oil contributes 45% of the total operational costs of fishermen, which must be borne while operating electric passenger boats. The search for alternative sources of electrical energy, especially solar powered electric boat, is carried out as an effort to overcome this problem. In this study, monitoring using the firebase application serves as the main means of data collection. To obtain real data on the voltage and electric current in the battery, researchers used the what if approach, where the program can read the input values ​​​​from the voltage and current sensors on the battery. By using the what if method, researchers want to obtain accurate battery charging and discharging test results and a level of truth approaching 100%. From the data analysis, the results showed that when charging the battery, the highest peak point occurred from 12.00 to 13.00 with a light intensity of 168080.40 Lux, a current of 10.57 amperes and a temperature of 32.20 0 C. While when discharging the battery, the lowest voltage value occurred at minute 45 of 71.28 volts, inversely proportional to the current of 41.26 amperes. This is due to the voltage drop in the battery to supply the 4000 Watt BLDC motor.